Positive Politeness Strategies in YouTube Comments: A Pragmatic Analysis of Kendrick Lamar’s “Money Trees” - Nesia Monika; Afriana (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examines the application of positive politeness methods in the YouTube comment area of Kendrick Lamar’s "Money Trees" music video, grounded in Brown and Levinson’s (1987) Politeness Theory. The study used a qualitative descriptive methodology to investigate the ways in which viewers convey admiration, emotion, and social connection in digital interactions. The data were collected from specific YouTube comments utilizing Sudaryanto’s (2015) observational method and were examined pragmatically. The findings indicate that commenters employ four categories of positive politeness strategies: Exaggerate (Interest, Approval, or Sympathy), Notice and Attend to the Hearer, Presuppose, Assert, or Raise Common Ground, and Intensify Interest to the Hearer. The Exaggerate technique is the most common of these, which means that fans often use over-the-top and passionate language to indicate how much they love the singer and the music. The employment of these tactics shows how language in digital spaces may bring people together, make them feel closer to each other, and make the online community more courteous and helpful. This study verifies that positive politeness is crucial in sustaining peaceful interactions within YouTube-based communication. Key words: Pragmatics, Positive Politeness, YouTube Comments, Kendrick Lamar, Money Trees